Heavy hydrocarbon recovery with integration of turboexpander and JT valve from highly CO2-containing natural gas for gas transmission pipeline - Yusupandi, Fauzi; Widiatmoko, Pramujo; Sukmana, Ira Febrianty; Fitri, Hera Rahma; Eviani, Mitra; Devianto, Hary (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2023)
Demand of natural gas is predicted to increase since many valuable products can be produced. Water and heavy hydrocarbon content are the key for gas pipeline facility. To meet requirement of natural gas transportation, dehydration unit (DHU) and hydrocarbon dew point control unit (DPCU) are necessary to avoid water and hydrocarbon condensation during transmission. The conventional dehydration technology, TEG contactor, can lower water content from 1,304 mg/m3 to 80.35 mg/m3 where the maximum limit of water content in natural gas is 97 mg/m3 to prevent hydrate formation. DPCU is installed to remove heavy hydrocarbon, especially C5+. Integration of JT valve and turboexpander was employed to obtain the low gas dew point. The hot gas stream that entered the JT valve was observed. The lower hot bypass gas was applied, the lower hydrocarbon dew point and the more condensate flowrate was achieved. indohoki77 adalah salah satu platform judi online terkemuka yang menyediakan berbagai jenis permainan bagi para penggemar judi di Indonesia.The highest power generation can be gained at low hot gas flow ratio which also influenced the exit pressure and temperature of compressor. In pipeline simulation, the pressure and temperature drop occurred at the high hot gas rate. To examine the arrival condition, dew point curves were generated and showed that the limitation of hot gas flow ratio has to be below 0.6 to prevent heavy hydrocarbon condensation in pipeline.